Antepartum myomectomy: a possible procedure for successful outcome - Chandran, Sabita Sai; Samal, Sunita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Though myomas usually remain asymptomatic during pregnancy, in one third of the cases they may increase in size and develop red degeneration. Majority of the cases will respond to medical management and rarely require surgical intervention. Site, size and number of the fibroids and the placental position are the important factors to be considered before intervention. Our case was having fibroid with placental attachment at its base and had features of rapid growth with red degeneration not responding to medical management and hence myomectomy was done in second trimester. In properly evaluated and carefully selected patients the procedure will be successful and improve the pregnancy outcome.